Detection of emerging HoBi-like Pestivirus (BVD-3) during an epidemiological investigation of bovine viral diarrhea virus in Xinjiang: a first-of-its-kind report - Yang, Ningning; Xu, Mingguo; Ma, Zhenguo; Li, Honghuan; Song, Shengnan; Gu, Xiaoxiao; Liu, Jingnan; Yang, Zhonglian; Zhu, Hongji; Ma, Hailong; Yi, Jihai; Wang, Yong; et al. (Frontiers in Microbiology, 2023)
Xinjiang pastoral area is the second largest pastoral area in China, accounting for 26.8% of the available grassland area in the country, and the geographical advantage of cattle breeding industry is very obvious. Bovine viral diarrhea virus (BVDV) has always been one of the important viral diseases that have plagued the development of cattle farming industry in the world. As one of the main pastoral areas of China's cattle farming industry, the Xinjiang pastoral area has also been deeply affected. In this study, 6,153 bovine serum samples were collected from 18 large-scale cattle farms in 13 cities in Xinjiang. The antibodies and antigens of 6,153 and 588 serum samples were detected by serological detection methods, respectively. Ten serum samples, which were antigen-positive by ELISA, were randomly selected for RT-PCR detection, sequencing, and phylogenetic analysis of suspected HoBilike pestivirus (HoBiPeV) strains. The results showed that the positive rates of BVDV antibodies and antigens were 53.68% (3,303/6,153) and 6.12% (36/588), respectively. One of the ten randomly selected seropositive samples was infected with the HoBiPeV strain. HoBiPeV, also referred to as BVDV-3, is an emerging atypical pestivirus that occurs in cattle and small ruminants, and its clinical signs are similar to those of BVDV infection. Based on the whole genome of the BVDV-3 reference strain (JS12/01) on the GenBank, the homology of the detected strain was 96.02%. The whole genome nucleotide sequence was submitted to the GenBank database, and the gene accession number was obtained: OP210314. The whole genome of isolate OP210314 was 12.239 nucleotides and contained a 5'-UTR of 340 nucleotides, a 3'-UTR of 199 nucleotides, and a large open reading frame (ORF) encoding a polyprotein consisting of 3899 amino acids. In conclusion, the prevalence rate of BVDV infection in Xinjiang dairy cows is high, and the genetic diversity is increasing. This study successfully identified and isolated HoBiPeV in Xinjiang for the first time, posing a potential threat to the cattle industry in Xinjiang.